Thioester deprotection using a biomimetic NCL approach - Villamil, Valentina; Saiz, Cecilia; Mahler, Graciela (Frontiers in Chemistry, 2022)
The reversibility of thiol-thioester linkage has been broadly employed in many fields of biochemistry (lipid synthesis) and chemistry (dynamic combinatorial chemistry and material science). When the transthioesterification is followed by a S-to-N acyl transfer to give an amide bond it is called Native Chemical Ligation (NCL), a high-yield chemoselective process used for peptide synthesis. Recently we described thioglycolic acid (TGA) as a useful reagent for thioester deprotection both in solution and anchored to a solid-supported under mild conditions. Inspired by NCL, in this work we extended this approach and explored the use of 2-aminothiols for the deprotection of thiols bearing an acyl group. The best results were obtained using cysteamine or L-cysteine in aqueous buffer pH 8 at room temperature for 30 min. The described approach was useful for S-acetyl, S-butyryl and S-benzoyl heterocycles deprotection with yields up to 84%. Employing this methodology, we prepared six new analogs 2 of mercaptomethyl bisthiazolidine 1, a useful inhibitor of a wide-range of Metallo-β-Lactamases (MBLs). Compared with the previous methodologies (TGA polymer supported and TGA in solution), the biomimetic deprotection herein described presents better performance with higher yields, shorter reaction time, less time-consuming operations, easier setup and lower costs.